Analysis of Hate Speech in Comment Sections Aceh TikTokers Accounts (Pragmatic Study) - Mulyani Mulyani; Syahriandi Syahriandi; Juni Ahyar (Universitas Negeri Semarang, 2025)
This study aims to describe the forms of hate speech in the comment sections of TikTok accounts HK, AA, FH, and SS, as well as the (pragmatic) meaning contained in each instance of hate speech found. This is a qualitative study using a descriptive approach. The research data consists of speech containing elements of hate in the form of words, phrases, clauses, and sentences. The data sources in this study are the TikTok application, focusing on the HK account (@herlin****02) on January 3, 2025, the AA account (@arif*****) on January 10, 2025, the FH account (@fatieh**** 24) on January 14, 2025, and the SS account (@She* Sau***) on January 17, 2025. In the data collection process, the author used three techniques: documentation, reading, and note-taking. The results of the study revealed a total of 57 instances of hate speech. The forms of hate speech obtained were divided into 5 parts as follows: 1) 28 instances of insults; 2) 12 instances of defamation; 3) 3 instances of blasphemy; 4) 10 instances of provocation/incitement; and 5) 4 instances of spreading false news. Furthermore, the pragmatic meaning found generally consists of phrases used to insult and mock Acehnese TikTokers for actions deemed highly inappropriate.